2020
DOI: 10.1016/j.jcct.2020.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for risk stratified use of cardiac computed tomography for congenital heart disease during the COVID-19 pandemic

Abstract: The impact of the coronavirus disease (COVID-19) pandemic in the United States and around the world has required significant changes to medical practice. Amidst the rapidly evolving public health emergency, hospital centers have been required to postpone elective procedures, preserve personal protective equipment (PPE), practice social distancing and limit staff exposures. Patients with congenital heart disease (CHD) often need urgent evaluation, most commonly for preprocedural evaluation. We have stratified t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The 14 selected studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were published in 2020. The results of this review revealed that all selected articles were published in international journals in English, totaling four countries, in which the vast majority, 10 articles, was produced in the United States of America (USA), followed by two publications in Italy, one in Europe and another in Australia.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 14 selected studies (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were published in 2020. The results of this review revealed that all selected articles were published in international journals in English, totaling four countries, in which the vast majority, 10 articles, was produced in the United States of America (USA), followed by two publications in Italy, one in Europe and another in Australia.…”
Section: Resultsmentioning
confidence: 99%
“…Level VII S3 (18) Recommendations for risk stratified use of cardiac computed tomography for congenital heart disease during the COVID-…”
Section: Consensus Among Expertsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Yellow fever virus’s ability at 40-50nm in width through with filtered human serum is worrying for our future use of blood products; Covid’s size ranges from 50-200nm. Use of blood products obtained by donation may therefore have uncertain deleterious consequences [ 1 , 3 ] .…”
Section: Changing Our Evaluation Diagnosis and Managementmentioning
confidence: 99%